Pemodelan 3d Dalam Film Animasi “Bukan Sekedar Teknologi” Menggunakan Metode MDLC - Khamilah Azizah; Damar Nurcahyono; Farindika Metandi (CV MEDAN TEKNO SOLUSI, 2024)
In the animation industry, especially in the production of 3D animated films, technological advancements have accelerated the growth and complexity of production. According to research conducted by the Indonesian Animation Industry Association (AINAKI) in 2020, data shows that the Indonesian animation sector grew by an average of 26% annually from 2015 to 2019. Therefore, animated films now require a high level of creativity and proficient technical skills. One of the key elements in 3D animation production is 3D modeling techniques. To enhance this, the research aims to gain a deeper understanding of 3D modeling techniques in the context of the short animation film “NOT JUST TECHNOLOGY” using the MDLC Method. Beta testing was conducted through interviews with 3D instructors at Enspire School of Digital Art (ESDA). The interview results showed that the 3D models created were in accordance with primitive modeling and polygonal modeling techniques. Additionally, the storyline and moral message of the film were clearly conveyed. Beta testing was also conducted through the distribution of questionnaires to 40 respondents, with a 89% approval rating on the Strongly Agree (SA) scale.